Feministisk institutionalisme og kommunal strukturreform - Hanne Nexø Jensen (The Royal Danish Library, 2009)
Feminist institutionalism and local government reform275 Danish municipalities were amalgamated into 98 in January 2007 and the percentages of female city managers were reduced drastically. I demonstrate how a combination of gender studies and new institutionalism contribute to an understanding of the gendered development in the municipalities. This is inspired by FIIN, The Feminism and Institutionalism International Network which was formed in order to contribute to studies of gender, politics, power and change combining elements from feminism and new institutionalism. Furthermore, I discuss the weak points in the theoretical contributions and suggest some possibilities of improvements ina relation to studies of public organisations undergoing change.